Combined anti-muscarinic and H2 receptor blockade in the healing of refractory duodenal ulcer. A double blind study. Issue 11 (November 1987) - Bardhan, K D; Thompson, M; Bose, K; Hinchliffe, R F; Crowe, J; Weir, D G; McCarthy, C; Walters, J; Thomson, T J; Thompson, M H
Abstract : The purpose of this study was to determine if pirenzepine and cimetidine given together was superior to cimetidine alone in inducing healing of refractory duodenal ulcers which remained unhealed after treatment with cimetidine or ranitidine for at least eight weeks. One hundred and thirty one patients from six centres were randomised to receive either cimetidine (C) 800 mg daily or cimetidine 800 mg plus pirenzepine (C + P) 100 mg daily under double blind conditions for six weeks. The healing rate was similar in both groups, irrespective of the method of calculation. On an intent-to-treat analysis, healing was: C 66%, C + P 57%, and amongst the patients who completed treatment, healing was 70% in both groups. Patients on C and on C + P experienced a similar decrease in daytime and in night time pain. Side effects of treatment, notably dry mouth and blurred vision, were reported more often by patients on combination therapy. Combined treatment with cimetidine plus pirenzepine in patients with refractory duodenal ulcer is unlikely to be beneficial.